Feminism in the Novel Ana Hurra by Ihsan Abdul Quddus: A Sociological Analysis of Literature - Maghfiroh, Faza Lailatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the manifestations and struggles of feminism in the novel Ana Hurra by Ihsan Abdul Quddus. Using a sociology of literature approach, this research dissects the text as a means of articulating feminine consciousness against patriarchal structures. The method employed is descriptive qualitative. The results indicate that the feminist struggle manifests in three primary points: the struggle to achieve the right to higher education, resistance against male dominance in the domestic sphere, and the courage to confront social stigma for the sake of personal independence. This study concludes that the novel Ana Hurra serves as a feminist manifesto asserting women’s rights to agency and full sovereignty in determining their own life paths.